IMPLEMENTASI VARIASI LARI KEDALAM PERMAINAN ANAK SEKOLAH DASAR - Zega, Agnes Kristiani; Nainggolan , Febriani; Gultom , Christy Evelyn; Silitonga , Ios Sudarno; Sembiring, Heka Maya Sari (ASOSIASI IDEBAHASA KEPRI, 2025)
Physical Education, Sports, and Health in elementary schools hold an important and strategic role in developing students’ individual potential. This is particularly crucial as elementary students are in a stage of rapid growth and development, requiring proper guidance and training. To optimize motor abilities, it is essential to provide fundamental movement learning that is appropriately designed according to their developmental level. One way to do this is by incorporating running variations into playful activities. Therefore, using variations of running in the form of games can enhance students’ interest and enthusiasm in participating in physical education lessons. This community service activity was carried out at UPT SDN 060934, Jl. Luku II, Medan Johor District, focusing on first-grade students. These students require enjoyable and developmentally appropriate movement-based learning to help them become more active while improving their speed and motor skills. The variations introduced were presented in the form of fun and engaging games that also incorporated coordination, teamwork, and concentration skills. Observation results showed a significant positive effect of running variation games on improving the motor skills of first-grade students in Physical Education learning at SDN 060934, Medan Johor.